Erbium-doped zinc-sodium phosphate glasses as high-gain material for integrated photonics - Rivera, Frida Flores (2024)
In this paper, we characterize erbium-doped sodium-zinc phosphate glasses' transmission loss and on-off gain coefficients. Results reveal that this material shows a transmission loss coefficient of 1.8 dB/mm and an on-off gain of 1.9 dB/mm for a 5 mm width sample, achieving net optical gain.